African elephant reintegration from captivity to wild living: quantifying the detailed behavioural changes - Tamara Eggeling; Tenisha Roos; Victoria L Boult; Brett Mitchell; TJ Steyn (Pachyderm)
There is increasing evidence of compromised welfare for captive African savannah elephants managed in confined spaces. With the trend for zoos and captive facilities to close due to public pressure, reflecting ethical concerns,  and thier limited capacity to manage 'difficult'  behaviours, elephants will continue to require rehabilitation into free-ranging areas or living in the wild. During reintegration from captivity into a free-roaming system, conservation management methods need to be carefully considered to ensure the individual’s welfare. Elephants,  have a sophisticated social life and exhibit complex body language employing a multitude of behavioural signals and gestures to demonstrate thier needs and feelings. These detailed signals could be valuable when assessing the welfare status of elephants as any large deviation in behaviour could indicate changes in elephant wellbeing. In this study,  a group of African elephants (Loxodonta africana) were monitored as they transitioned from captivity to a free-roaming system. To track the impact of reintegration on elephant welfare, we recorded  frequencies of behaviours categorized as Ambivalent, Assessing, Frustrated, and Social, and ofspecific  behaviours within each category, across four phases of reintegration into the wild (Stables, Boma, Release and Free). Significant differences in rates between reintegration phases were observed for several categories of behaviour and specific behaviours. Decreased  frequencies of Frustrated behaviours and an increase in social behaviours when the elephants were Free were potentially indicative of improved welfare in wild settings. We conclude that monitoring of  behaviours is important when assessing elephant welfare, and to establish the success of reintegration operations.